The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0065114
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating Endothelial Cells in Refractory Pulmonary Hypertension in Children: Markers of Treatment Efficacy and Clinical Worsening

Abstract: BackgroundPulmonary vasodilators in general and prostacyclin analogues in particular have improved the outcome of patients with pulmonary arterial hypertension (PAH). Endothelial dysfunction is a key feature of PAH and we previously described that circulating endothelial cell (CEC) level could be used as a biomarker of endothelial dysfunction in PAH. We now hypothesized that an efficient PAH-specific vasodilator therapy might decrease CEC level.Methods/ResultsCECs were prospectively quantified by immunomagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 37 publications
1
39
0
3
Order By: Relevance
“…In addition to microparticles, circulating endothelial cells (CECs) and endothelial progenitor cells (EPCs) are present in the blood of individuals with PH [43,44]. CECs have been prospectively measured in IPAH pediatric demographic as well as PAH secondary to CHD, prior to and after therapeutic treatment [45]. Furthermore, increased levels of CECs are associated with irreversible PAH due to congenital heart defects [42].…”
Section: Microparticles and Circulating Endothelial Cellsmentioning
confidence: 99%
“…In addition to microparticles, circulating endothelial cells (CECs) and endothelial progenitor cells (EPCs) are present in the blood of individuals with PH [43,44]. CECs have been prospectively measured in IPAH pediatric demographic as well as PAH secondary to CHD, prior to and after therapeutic treatment [45]. Furthermore, increased levels of CECs are associated with irreversible PAH due to congenital heart defects [42].…”
Section: Microparticles and Circulating Endothelial Cellsmentioning
confidence: 99%
“…48 Furthermore, in patients with idiopathic or CHD-associated refractory PAH, circulating endothelial cells were significantly decreased after the introduction of endothelin-receptor antagonists and/ or phosphodiesterase 5 inhibitors and/or subcutaneous treprostinil, and rose before clinical deterioration. 52 In contrast, other biomarkers of endothelial activation, regeneration and injury, method of estimating cardiac output and PVR using impedance cardiography, Non Invasive Cardiac System (NICaS) and echocardiography was shown to have a good correlation with right heart catheterization Fick-calculated PVR (receiver-operating characteristic area under the curve (ROC AUC) 0.92, sensitivity 80.3%, specificity 100%) but not with thermodilution (ROC AUC 0.84, sensitivity 81.3%, specificity 75%). 24 Acute vasodilator testing is used to test the reactivity of the pulmonary vascular bed, 1 either with oxygen 25 or inhaled nitric oxide (iNO).…”
Section: Myers Po Et Almentioning
confidence: 99%
“…CECs are increased in vascular injury-related disorders such as acute myocardial infarction and unstable angina (7). Data on CEC numbers in PAH are sparse and have been gathered in small patient populations only (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Regarding this, it is important to note that CECs are increased in pediatric patients with PAH and can be used to discriminate between reversible and irreversible PAH associated with cardiovascular shunts in congenital heart disease (9). Furthermore, the same group showed that CEC numbers in children with PAH are associated with clinical worsening and the treatment efficacy of trepostinil (11). This article has an online supplement, which is accessible from this issue's table of contents at www.atsjournals.org…”
mentioning
confidence: 99%